Aroma compounds in fresh and dried mango fruit (Mangifera indica L. cv. Kent): impact of drying on volatile composition. (18th January 2016) - Bonneau, Adeline; Boulanger, Renaud; Lebrun, Marc; Maraval, Isabelle; Gunata, Ziya
Summary: Volatile compounds from fresh and dried mango were extracted by the solvent‐assisted flavour evaporation (SAFE) technique and analysed by GC‐MS. Forty‐one and fifty five volatile compounds were identified in fresh and dried mango, respectively. Monoterpenes, followed by sesquiterpenes, lactones and alcohols were the major compounds. Drying induced substantial losses of several compounds. The total amount of volatiles decreased by about 59%. These losses could be mainly attributed to the evaporation of the volatiles during drying, the extent of which seemed to increase with the hydrophobicity and Henry's law constant of the compounds. However, new compounds appeared and enrichment of some compounds was observed after drying. Limonene, β‐myrcene, δ‐3‐carene, β‐caryophyllene, γ‐butyrolactone and 3‐methylbutyl butanoate were found to be flavour contributors in both products on the basis of the odour activity values (OAVs). Mesifuran displayed high OAV only in fresh fruit while hexanal and heptanal only in dried mango. Abstract : The volatile composition of fresh mango fruit significantly changed under drying. Drastic losses occurred for some compounds mainly for terpenoids. On the other hand, new compounds appeared such as alcohols, aldehydes and Maillard volatiles. On the basis of odour activity value (OAV), six compounds were odor contributors in both products consisting mainly of terpenoids, γ‐butyrolactone and 3‐methylbutyl butanoate. Mesifuran was the odor contributor only in fresh fruit, whereas hexanal and heptanal was the odor contributor in dried fruit.